Development of a behaviour change intervention to increase care home staff influenza vaccination uptake - Amrish Patel; Sion Scott; Alys Wyn Griffiths; David Wright (International Journal of Nursing Studies Advances, 2025)
Background: To protect care home residents the World Health Organisation recommends that 75 % of care home staff are vaccinated for influenza. In the UK this value is less than 30 %. Previously reported interventions have not been informed by theory and usually only addressed one or two known barriers to uptake. Using behavioural science, we worked with care home staff to develop an intervention which addressed all barriers at both individual and care home level. Methods: We developed an online questionnaire, derived from the literature, asking staff about barriers and facilitators of flu vaccination. These were prioritised (based on frequency and distinctiveness), then mapped to the Theoretical Domains Framework. Relevant behaviour change techniques were identified. Care home staff selected and designed behaviour change techniques according to affordability, practicability, effectiveness, acceptability, safety and equity (APEASE) via an online questionnaire and workshop. Results: The prioritised barriers were: lack of time to get vaccinated; insufficient vaccine supplies; vaccination costs; a lack of peers getting vaccinated and beliefs that staff do not need vaccination and that it is ineffective. Six behaviour change techniques were selected and developed into a multi-component intervention: (behaviour change technique 1, Restructure of the physical environment) Free, in care home vaccination clinics for staff; (behaviour change techniques 2–4, Information about health consequences, Salience of consequences and information about others’ approval) information campaign featuring care home staff highlighting non-vaccination risks, (behaviour change techniques 5–6, Information about health consequences and Credible source) information campaign featuring primary care doctor challenging misconceptions. Conclusions: We developed the first theory and evidence-based intervention specifically to facilitate care home staff flu vaccination uptake. Feasibility and acceptability testing of the intervention followed by definitive trial to assess efficacy in care homes is necessary to inform policy decision-making.